2004
DOI: 10.1001/archneur.61.11.1699
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy in HIV Infection

Abstract: No direct benefit of neuroactive HAART therapy was found in patients with advanced human immunodeficiency virus infection. However, in neuropsychologically impaired patients, there was a benefit in memory function. This suggests that a threshold of neuropsychological impairment is required for the benefit of neuroactive HAART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…However, HAART may not prevent HIV-induced neuronal damage even when viral load is low (28). Progressive CNS damage is now more common as patients live longer and is somewhat resistant even to therapeutic agents that cross the blood-brain barrier (29). The incidence of HIV-related neuropathology at autopsy also has increased since HAART therapy became more widely available (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, HAART may not prevent HIV-induced neuronal damage even when viral load is low (28). Progressive CNS damage is now more common as patients live longer and is somewhat resistant even to therapeutic agents that cross the blood-brain barrier (29). The incidence of HIV-related neuropathology at autopsy also has increased since HAART therapy became more widely available (28).…”
Section: Discussionmentioning
confidence: 99%
“…Recently though, there has been an increasing number of studies showing the benefit of a CNS penetrating regimen (Cysique et al 2004b;Letendre et al 2004) in achieving a more favorable clinical outcome. The nature of a CNS penetrant regimen is the subject of ongoing studies but according to one group a central nervous system penetration effectiveness score of 3 or more is associated with a (Letendre et al 2008).…”
Section: Optimization Of Haartmentioning
confidence: 99%
“…For example, one study demonstrated a positive association between CPE scores and neurocognition limited to a subset of HIV+ participants with neurocognitive impairment at baseline (Cysique, Maruff & Brew, 2004), indicating that premorbid clinical status prior to initiation of cART may be an important determinant of the relationship between CPE and neurocognitive status. Similarly, Tozzi et al (2007) reported persistent neurocognitive deficits correlated with baseline neurocognitive impairment in a HIV+ cART-treated sample.…”
Section: Introductionmentioning
confidence: 99%